"Diagnosis of Hemophilia B Carriers, Using Taq I and Xmn I Polymorphisms of the FactorIX Gene in Iranian Individuals" - P Ghandil; DD Farhud; S Zeinali; A Ghadiri (Tehran University of Medical Sciences, 2003)
Hemophilia B is factor IX deficiency and is inherited as X-linked recessive disorder. The subject of carrier detection in hemophilias has received new impetus in the last several years. Analysis of factor IX gene polymorphisms is considered the best approach for prenatal diagnosis and hemophilia B carrier detection, if the identification of the gene mutation is possible. Allele frequencies of two intragenic RFLP (Xmn I and Taq I) was investigated in 100 Iranian families. For some families, carrier's detection was done using this method. The results indicated that RFLP segregation analyses provide a useful method for carrier detection in hemophilia B.